Escalator or Step Stool? Gendered Labor and Token Processes in Tech Work. Issue 5 (October 2019) - Alegria, Sharla
Gender scholars use the metaphor of the "glass escalator" to describe a tendency for men in women-dominated workplaces to be promoted into supervisory positions. More recently, scholars, including the metaphor's original author, critique the glass escalator metaphor for not addressing the intersections of gender with other relevant identities or the ways that work has changed in the twenty-first century. I apply an intersectional lens to understand how gender and race shape women's career paths in tech work, where twenty-first century changes to the organization of workplaces are common. I build on theories of raced and gendered labor and the glass escalator to make sense of women's careers in a contemporary field dominated by men. I find some evidence that white women, but not women of color, experience something similar to a "glass escalator" where they are promoted into management, but those promotions are a smaller step up—more step stool than escalator. These promotions move women out of technical positions and towards business and management, releasing engineering teams from the pressure to fully incorporate women.